2012
DOI: 10.1371/journal.pone.0045341
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Stereo Camera-Based Upper Extremity Workspace Evaluation in Patients with Neuromuscular Diseases

Abstract: BackgroundThe concept of reachable workspace is closely tied to upper limb joint range of motion and functional capability. Currently, no practical and cost-effective methods are available in clinical and research settings to provide arm-function evaluation using an individual’s three-dimensional (3D) reachable workspace. A method to intuitively display and effectively analyze reachable workspace would not only complement traditional upper limb functional assessments, but also provide an innovative approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
0
36
1
Order By: Relevance
“…In this paper, we follow up on the previously published work16 by evaluating the validity, reliability, and sensitivity of the developed methodology and the outcome measurement. The results support discriminant validity of the developed methodology and outcome measure by demonstrating significant difference in the total reachable workspace RSA between healthy able-bodied controls and patients with NMDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we follow up on the previously published work16 by evaluating the validity, reliability, and sensitivity of the developed methodology and the outcome measurement. The results support discriminant validity of the developed methodology and outcome measure by demonstrating significant difference in the total reachable workspace RSA between healthy able-bodied controls and patients with NMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an innovative method to measure and graphically reconstruct an individual’s upper extremity 3D reachable workspace using a low-cost single stereo camera sensor system was developed by the study investigators 16. The results showed that a single stereo camera system was capable of capturing and reconstructing 3D reachable workspace that was robust, fast, with minimal loss of data points when compared against full-scale motion analysis system simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Different applications and developments concerning the use of 3D simulation tools for the evaluation of workstations can be read in the scientific literature, successfully describing the use of these tools for the design and improvement of workstations [6–9]. In addition, different studies associate the improvement of ergonomics with quality and productivity improvement [1013].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic algorithms have been used to set the parameters of the exoskeleton to maximize the range of motion [5]. Recently, clinical reachable workspace metrics have been developed to quantify an individual's range of motion using a Kinect camera [15,10]. In the controls community, there are various methods to compute the reachable set of a dynamical system which include: Hamilton-Jacobi Methods [20], support function methods [8], sum-of-squares programming [24,26], and occupation measures [19].…”
Section: Prior Workmentioning
confidence: 99%